Reconsidering nearshoring to avoid global crisis impacts: Application and calculation of the total cost of ownership for specific scenarios. (June 2022) - van Hassel, Edwin; Vanelslander, Thierry; Neyens, Kris; Vandeborre, Hans; Kindt, Dominique; Kellens, Stefan
Abstract: With the 2020 emergence of the COVID-19 pandemic, many production companies have re-inforced the rethinking their strategies of production location. In the 1980's and 1990's, one has witnessed a substantial shift of production activities. Increasing production activities led to increasing wage levels and land rents in developing countries since. COVID-19 may be a trigger that will re-inforce the nearshoring process. This paper develops and applies a framework with a quantitative and a qualitative part, so as to verify how a selected nearshoring candidate country performs. The quantitative part relies on a chain cost calculation model, while the qualitative part uses appreciations given by the decision maker to 'time', 'value' and 'cost'. The framework is applied to a case with production located in China. In doing so, it is important to determine which sector one belongs to, since different characteristics will play a different role depending on the sector. Furthermore, transport costs typically do not have the biggest share in total supply costs, but may be decisive as they determine also the lead time and hence the costs related to stocks. Finally, it turns out that qualitative decision factors – rather linked to perception and personal preferences – do not always match economic outcomes. Highlights: The nearshoring tendency, got further impetus recently by the COVID-19 pandemic, the long-lasting effect of which is to be seen. Industries with high value-added products will behave differently from those with low value-added. Transport costs may contribute to the gains made by nearshoring when calculating the total cost of ownership (TCO). Qualitative elements – rather linked to perception and personal preferences – do not always match economic outcomes.